Treatment burden among people with chronic illness: what are consumer health organizations saying?. (September 2013) - Sav, Adem; McMillan, Sara S; Kelly, Fiona; Kendall, Elizabeth; Whitty, Jennifer A; King, Michelle A; Wheeler, Amanda J
Objectives: To explore the perspectives of consumer health organizations about the burden of chronic illness and multiple treatment regimens experienced by the consumers they represent. Methods: In-depth interviews (n = 15) were conducted with senior representatives from peak Australian consumer health organizations representing diabetes, asthma, cardiovascular disease, cancer, musculoskeletal illness and mental health. Results: Medication burden, which included aspects such as multiple medications, side effects, stigma and adverse events resulting from medication use, emerged as the most significant and prevalent theme. Carer burden and the negative impact of financial burden was widely discussed, particularly for low-income earners with claims that these consumers were forced to prioritise medications according to how effective they perceived them to be. Time taken to learn about treatment, administer, and monitor or travel to obtain treatment also emerged as being burdensome, however, difficulty accessing treatment was considered to be particularly burdensome. The disjointed nature of care among healthcare services was thought to create a sense of confusion and distress. Discussion: Many of the issues discussed by participants corroborated existing research, underscoring the complementary provider, and advocacy role of these organisations in mitigating treatment burden for people with chronic illness.